A TERRITORIAL RIGHTS PROVISION ALLOWING FOR THE ENTRY OF FOREIGN INVESTMENTS - Pelawi, Jhon Tyson; Ismansyah; Lubis, Muhammad Yamin; Marlina; Rosmalinda (Ultimate Journal of Legal Studies, 2024)
One of the main issues that arises when investors plan to make investments in Indonesia is the transfer of land rights to one of the five investment barriers, which are connected to obstacles to land certification, building licenses, and land zoning. This effort discusses how problems involving land transfers are handled by national criminal law and how giving foreign investors legal certainty is achieved by the effectiveness of criminal legislation against land transfers. The aim of this research is to find out whether criminal law can resolve disputes related to the transfer of land rights so as to provide certainty and security for foreign investors regarding the transfer of land rights. by investigating problems through normative legal research or legal research carried out in libraries using a jurisprudential approach and theory of legal objectives, we will get solutions to existing problems so that this research provides qualitative research results based on the data and theory used. The study's findings lead to the conclusion that Article 52, paragraphs (1) and (2) of the UUPA, which deals with criminal laws against the transfer of land rights, regulates the criminal law of land area for its infringement. The form of attained legal certainty in the transfer of land rights for investors is provided by the effectiveness of criminal law in enforcing the law against communities that occupy property over the subject matter.